ANALISIS PENYERAPAN TENAGA KERJA SEKTORAL SERTA PENGARUHNYA TERHADAP PEMBANGUNAN MANUSIA DI KOTA SAMARINDA (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
Development is a step to create something that does not exist be there or make a change that makes things better or increased. The national development based on equitable development and as a result, economic growth and national stability high enough healthy and dynamic. Based on BPS data Samarinda employment in the services sector has the largest number of workers first, followed by the Industry business sector and the agriculture sector. The increase in the number of employment on average coupled with a rise in the index of human development from year to year. Based on these data to analyze the extent of absorption of labor both sectors Agriculture, Industry and Services had a positive influence on human development index in Samarinda. Simultaneously, there is the influence of sector employment Agriculture, Industry and Services to the Human Development Index of Samarinda in 2005 - 2014. Employment Agriculture sector has the most influence on the growth of the Human Development Index Kota Samarinda in 2005-2014 compared to the other two sectors of employment. Keywords: The Human Development Index, HDI, Labor